How COVID-19 is Affecting Apprentices - Shamaila Hassnain; Naureen Omar (BioMedica, 2020)
Background and Objective: Coronavirus induced disease (COVID-19) is affecting people all around the world. The rising number of deaths due to COVID-19 is not only harassing people but also causing strong emotions in adults as well as in children due to anxiety, fear and stress. The objective of this study was to assess the fears, anxiety and stress due to COVID-19 pandemic and related issues among the apprentices at various levels in different parts of world. Methods: It was a cross sectional survey design to assess the students/trainee’s immediate psychological response during COVID-19 outbreak by using an anonymous online questionnaire. A snowball sampling technique was conducted focusing general public all around the world from 3rd April 2020 till 7th April 2020. A total of N=354 participants filled the form completely. The structured questionnaire collected information on demographic data and psychological aspect of this outbreak, including extreme fear and uncertainty. Results: A total of N = 354 participants completed the questionnaire; majority were from the age group of 21–30 years. Approximately 66.4% were females and 33.6% males. Participants from Asia were 83.6% while 9.9%, 3.4%, 2.8% and 1% from America/Canada, Europe, Africa and Australia respectively. Out of n = 354 participants 59.3% were relying on health professionals for authentic source of information regarding COVID-19 while 16.4%, 15% and 5.4% considered social media, television and World Health Organization (WHO) website respectively as their authentic guide. Out of the (n = 354) participants 80.5% were afraid about health status during COVID-19 most predominantly females (66.3%) (P = 0.000). A total of 65.8% participants felt agitated or irritated in this outbreak. Conclusion: COVID-19 lockdowns are affecting both physical and mental health of students and apprentices enrolled at different levels of education. Females are more affected and concerned to their loved ones and themselves. Working norms are being maintained and responsibilities are being fulfilled despite this grave situation.